2019
DOI: 10.31832/smj.544455
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinde Ağrı, Aleksitimi, Emosyonel Durum ve Yaşam Kalitesinin Değerlendirilmesi

Abstract: Orcid :Mehmet Kurtaran: https://orcid.org/0000-0001-8257-4400 Seda Baktır: https://orcid.org/0000-0002-3753-5135 Ebru Şeker Abanoz: https://orcid.org/0000-0002-7810-3654İpek Yeldan: https://orcid.org/0000-0002-6344-4157 ARAŞTIRMA MAKALESİ / Research Article ÖzAmaç Bu çalışmada üniversite öğrencilerinde kas-iskelet sistemi şikayetleri, duyguları tanıma ve açıklamada zorluk olarak tanımlanan aleksitimi, depresif belirti yaygınlığı ve yaşam kalitesi arasındaki ilişkiyi incelemek amaçlandı. ( Sakarya Tıp Dergisi 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Baş ve ark. 'nın 2007 yılında yaptıkları çalışmalarında enerji harcaması ve fiziksel aktivite ilişkili bulunmuş, sedanter davranışın sağlığı olumsuz etkileyebileceği belirtilmiştir 29 . Aynı şekilde Yılmaz ve Karaca' nin 2019 yılında üniversite öğrencilerinde yaptıkları çalışmalarında sedanter davranışların sağlıklı yaşam ve yaşam kalitesi üzerine olumsuz etkileri olduğu belirtilmiştir 30 .…”
Section: Discussionunclassified
“…Baş ve ark. 'nın 2007 yılında yaptıkları çalışmalarında enerji harcaması ve fiziksel aktivite ilişkili bulunmuş, sedanter davranışın sağlığı olumsuz etkileyebileceği belirtilmiştir 29 . Aynı şekilde Yılmaz ve Karaca' nin 2019 yılında üniversite öğrencilerinde yaptıkları çalışmalarında sedanter davranışların sağlıklı yaşam ve yaşam kalitesi üzerine olumsuz etkileri olduğu belirtilmiştir 30 .…”
Section: Discussionunclassified
“…However, with increasing evidence, it has been reported that J Basic Clin Health Sci 2023; 7: 660-670 Yuksel A et al Chronic Pain and Adherence to the Mediterranean Diet studying for long hours in the same position often creates physical stress, and their efforts to achieve academic success create psychological stress and these stresses cause musculoskeletal pain (4). In another study, which reported that CP is common among university students, it was found that the students mostly experienced CP in the musculoskeletal system, with upper back pain in 49.2%, neck pain in 43.7%, and lower back pain in 40.2% (5). Like most diseases, CP is often caused by a combination of multiple or a series of events.…”
Section: Introductionmentioning
confidence: 99%